Comparative field studies of various traps and attractants for the Mediterranean fruit fly Ceratitis capitata (Diptera: Tephritidae) in fall - Liaropoulos, K.; Zervas, G.; Mavraganis, V.; Broumas, T.; Tsiropoulos, G.; Tsirogiannis, V. (ENTOMOLOGIA HELLENICA, 2004)
To clarify questions regarding the effectiveness of the many different types of traps and semiochemicals used for the monitoring and the control of the Mediterranean Fruit Fly, Ceratitis capitata (Wiedemann) (Diptera: Τephrititae), seven trap types, four food attractants, one sex attractant and a combination of food and sex attractant, were evaluated under field conditions in orange orchards in fall. No major differences were observed between trap designs resembling the original McPhail glass trap. The plastic bottle trap of 1,5L volume, with four side openings for one-way fly entrance, proved very efficient when filled with a proteinaceous food attractant Ζ1. From the attractants, two of them, Ζ1 and Entomela showed the best performance. The combination of food and a sex attractant showed no significant synergistic effects on trap efficiency. The findings allow a better choice among trap types and attractants, available today in the market, for Medfly monitoring and control.